1973
DOI: 10.1172/jci107486
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Antibody to Gonococcal Pili. CHANGES IN ANTIBODY LEVELS WITH GONOCOCCAL INFECTION

Abstract: A B S T R A C T Gonococcal pili, pure by the criteria of electron microscopic examination and polyacrylamide gel electrophoresis in sodium dodecyl sulfate, have been prepared by repeated cycles of precipitation with 0.1 M MgCli, followed by dissolution in 0.01 M Tris pH 8, 0.01 M NaNs. Using a fluorescein-conjugated antibody prepared to pili from a single strain, pilar antigen(s) was found to be present in each of 18 strains of gonococci tested, and absent from strains of pilated meningococci, nonpathogenic Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
2

Year Published

1975
1975
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 58 publications
4
45
2
Order By: Relevance
“…These two strains were of different gonococcal serotypes as tested and described by Johnston and Gotschlich (5) . Different serotypes of gonococci were picked to insure that the gonococcal strains studied were distinctly different, since previous studies indicated antigenic similarity of pili from many gonococci (2,3) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These two strains were of different gonococcal serotypes as tested and described by Johnston and Gotschlich (5) . Different serotypes of gonococci were picked to insure that the gonococcal strains studied were distinctly different, since previous studies indicated antigenic similarity of pili from many gonococci (2,3) .…”
Section: Methodsmentioning
confidence: 99%
“…Colony type 2 gonococci were grown in liquid culture as previously described (2,6) . At the height of log phase growth, the liquid culture was briefly sheared in an omnimixer (Dupont Instruments, Sorval Operations, Newtown, Conn .)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pili, which are associated with enhanced virulence in humans (Kellogg et al, 1963), are responsible for increased attachment in vitro, probably by overcoming the initial electrostatic repulsive force between the gonococcus and its host cell (Heckels et al, 1976). Raised levels of anti-pilus antibodies have been reported in patients with gonorrhoea, an observation which suggests that the detection of such antibodies might provide a serological screening system (Buchanan et al, 1973).…”
Section: Introductionmentioning
confidence: 99%